Kampung Madani As An Effort To Alleviate Poverty In Bangkingan Sub-District Surabaya - Listyorini, Dyah; Mustofa, Amirul; Sunarya, Aris (Pt. Anagata Sembagi Education, 2025)
The study's goal was to assess how well the Kampung Madani programme worked to reduce poverty. The study was conducted in Surabaya's Bangkingan Village. Interviews and document data utilising qualitative research and interactive analysis were the methods utilised to obtain the data. Condensing data, presenting data, and generating conclusions were the three primary steps of the interactive analytic approach that was employed. According to this report, the Kampung Madani program's successful reduction of severe poverty to zero was made possible by the active involvement of the community and cooperation with the commercial sector through corporate social responsibility. An inclusive and long-lasting empowerment paradigm was produced by the cooperation of the public, corporate, and governmental sectors. The Kampung Madani Program's research in Bangkingan Village showed that strong community involvement and cooperation with the commercial sector through corporate social responsibility (CSR) were key to the program's success in eradicating severe poverty. An inclusive and long-lasting empowerment paradigm was developed as a result of the government, community, and commercial sector working together. Other areas may use its execution as a model when creating comparable initiatives to effectively reduce poverty.